Cluster randomized multilevel intervention for promoting physical activity in rural communities - Beck, Alan M.; Serrano, Natalicio; Duncan, Dixie; Eyler, Amy A.; Gilbert, Amanda; Naghiloo, Fatemeh; Reis, Rodrigo; Tabak, Rachel G.; Brownson, Ross C. (Frontiers in Public Health, 2025)
IntroductionRural areas of the United States have lower levels of physical activity (PA) as compared to their urban and suburban counterparts, leading to higher levels of chronic diseases. The objective of the study was to increase PA in rural communities via a multilevel intervention.MethodsWe implemented a cluster randomized controlled trial of a community-based multilevel PA intervention between 2019 and 2022 in 14 rural communities. The intervention consisted of (1) text messaging (i.e., individual level), (2) encouragement of walking groups (i.e., interpersonal level), and (3) community-based marketing (i.e., community level).ResultsParticipants meeting the 2018 PA guidelines for aerobic PA increased among the intervention group, with no differences in recreational, occupational, transportation, or total PA.DiscussionIn this multilevel study the intervention is associated with meeting PA guidelines. The complexities of the impact of COVID-19 make it hard to disentangle the effects of the intervention on PA and other outcomes. Though the main tenets of the multilevel intervention had to be altered due to the pandemic, there was value in text messaging in rural areas to promote PA. Future studies should consider incorporating text messages into rural areas as a component of a PA promotion campaign.Clinical trial registrationClinicaltrials.gov, identifier NCT03683173.